This preview shows page 1. Sign up to view the full content.
Unformatted text preview: is S [ x ] B = [ x ] E , and that you are looking for the matrix M such that M [ x ] B = [ T ( x )] B . Since A [ x ] E = [ T ( x )] E , substituting gets you AS [ x ] B = S [ T ( x )] B , and M = S-1 MS . In this case that is [ 3 5 1 2 ][ 3 4-1-1 ][ 2-5-1 3 ] = [ 3 5 1 2 ][ 2-3-1 2 ] = [ 1 1 1 ] . You could also do this by the one of the other methods discussed in Bretscher, but, when the inverse of S is easy to nd, the method here is easy....
View Full Document
- Fall '08